Edukasi Perilaku Personal Hygiene Remaja : Upaya Mencegah Fluor Albus di Pondok Pesantren Sabilil Muttaqien - Cintika Yorinda Sebtalesy; Lucia Ani Kristanti (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The period of puberty or adolescence is a period of maturation of the reproductive organs that lasts between the ages of 10-19 years. In young women, it is marked by the occurrence of menstruation. One of the main things that must be considered is personal hygiene. One of the problems that can arise due to lack of personal hygiene is the occurrence of vaginal discharge (fluor albus). If ignored, it can trigger early symptoms of cervical cancer, the incidence of which is around 15,000 new cases in Indonesia, which can end in death. Eight out of ten young women at the Sabilil Muttaqien Islamic Boarding School, Takeran District, Magetan Regency experience vaginal discharge. Some of them experienced vaginal discharge with yellow stains on their underwear and sometimes felt itchy, while 2 teenagers who did not understand personal hygiene also experienced vaginal discharge, some were physiological, some were pathological and did not know about personal hygiene. For this reason, it is necessary to hold health education about personal hygiene to prevent the occurrence of fluor albus by using lecture and question and answer methods. The result of this activity is that students know about personal hygiene, so that behavior will change.